Innovation strategies and network configurations in knowledge-intensive services - Salavisa, I. (2015)
In this paper we deal with the innovation strategies of software for telecommunications companies that develop innovative products through the creation, use and adaptation of various resources. In addition to in-house capabilities and resources, they resort to external sources via market and non-market transactions. We will focus on non-market exchanges, namely networks. The main goal is to determine if different innovation strategies (mostly radical versus mostly incremental) are associated with distinct networking strategies. With this aim, we adopted a specific analysis of innovation networks, which deals separately with the two main types of resource: knowledge and complementary assets. Results reveal that there are clear-cut differences in the network configurations of radical versus incremental innovators, particularly in the access to knowledge. They also give support to the adequacy of using a fine-grained analysis. These findings can therefore add to the debate on the most favourable networking strategies for innovation.